2021
DOI: 10.3390/aerospace8050136
|View full text |Cite
|
Sign up to set email alerts
|

Eeloscope—Towards a Novel Endoscopic System Enabling Digital Aircraft Fuel Tank Maintenance

Abstract: In this research article, a novel endoscopic system, which is suited to perform a digital inspection of the aircraft wing fuel tanks, is introduced. The aim of this work is to specifically design and develop an assisting system, called `Eeloscope’, to allow accessing and diving through an aircraft kerosene tank in a minimally invasive matter. Currently, mechanics often suffer from the harsh working environment and the arduous maintenance duties within the tank. To address such challenges and derive a tailored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…The eye tracking recordings further showed significant differences between the different groups of expertise, which was in accordance with previous work [13,35,39,48]. A review of the gaze plots revealed that inspectors made fewer fixations than engineers and assembly operators.…”
Section: Inspection Approachsupporting
confidence: 90%
“…The eye tracking recordings further showed significant differences between the different groups of expertise, which was in accordance with previous work [13,35,39,48]. A review of the gaze plots revealed that inspectors made fewer fixations than engineers and assembly operators.…”
Section: Inspection Approachsupporting
confidence: 90%
“…However, the planning of shared activities is not trivial, since the intrinsic task hazard reduction through robot takeover could lead to a complete procedural change of the working routine. For instance, supporting preparation and/or safety surveillance activities related to repair and maintenance processes, as well as the human resources required to support their realization, could become redundant ( Heilemann et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…36 Various approved methods, such as the jet fuel thermal oxidation tester (JFTOT), rapid small-scale oxidation test (RSSOT), oxidation stability test (OST), and rotating bomb calorimeter (RBC), 30 evaluate the thermal oxidative stability, a crucial requirement of aviation fuel. These tests, sanctioned by organizations like ASTM International and the International Civil Aviation Organization (ICAO), 36,60 offer vital information into the fuel's stability, reactivity, and compatibility with systems and engines, enhancing the overall reliability. Recognizing the impact of the molecular structure on the induction period (IP), a key measure of oxidative stability, is crucial for refining the thermal oxidative properties of SAFs and ensuring their secure and dependable use in aviation.…”
Section: High Flash Pointmentioning
confidence: 99%